Adaptation of "Nicholson McBride Resilience Questionnaire" (NMRQ) in Greek. A reliability and validity study in an epidemiological Greek sample - Pilafas, Georgios; Strongylaki, Nefeli Paraskevi; Papaioannou, Dimitrios; Menti, Despina; Lyrakos, Georgios (Health & Research Journal, 2020)
Introduction: ‘Psychological Resilience’ is one of the key elements in human behavior that interplays with stress in mental disorders and physical illnesses in both healthy and unhealthy populations, regardless of their biopsychosocial background. Therefore, a reliable and valid resilience questionnaire for clinical and research use is of great necessity. Aim: Hence, the present study was conducted in order for the original English version of ‘Nicholson McBride Resilience Questionnaire’ (NMRQ) to be adapted in the Greek population. Methods & Materials: The original English NMRQ consists of 12 items measuring resilience. It is a self-reported questionnaire, while each respective item is measured through a 5-Likert scale point system. The design of the study was developed to firstly translate the original English questionnaire in Greek, and secondly to test the new version upon its ‘item consistency’, ‘internal correlation’, ‘internal consistency’, ‘consistency validity’, and finally perform a ‘factor analysis’ after recruiting a Greek sample. Results: The results show 80% validity (Cronbach’s alpha=.800) of the new Greek version. The number of participants (N= 1,158) provided to the study an ‘a priori’ odds ratio of 1.274, a critical z of 1.6448 and an actual power of 95%. The Greek translation was considered accurate, while the new version maintained a good item consistency. Conclusion: It is proposed that the Greek version of NMRQ may be adapted in the Greek population in clinical and research related to resilience and stress, as well as for any future studies to test-retest its validity and reliability.